Answer:
![y = (3)/(4)x + (19)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6eq4vve2zf89q7rdyapv7mq12gxyqq3udv.png)
Explanation:
We have to get the equation of the straight line through the points (3,7) and (-1,4).
Now, we know that the two-point formula of a straight line passing through the two points
and
is given by
.
So, in our case, the equation of the straight line will be
![(y - 7)/(7 - 4) = (x - 3)/(3 + 1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2y57hblubyxsephhciysr22yrcjs4ikfes.png)
⇒ 4(y - 7) = 3(x - 3)
⇒ 4y - 28 = 3x - 9
⇒ 4y = 3x + 19
⇒
(Answer)